Analysis of Piperine in Black Pepper by High Performance Liquid Chromatography - Shrestha, Suraj; Chaudhary, Nibedita; Sah, Rajkumari; Malakar, Neera (Journal of Nepal Chemical Society, 2020)
Piperine is the most important alkaloid present in the black pepper. A high performance liquid chromatography (HPLC) method proposed by International Organization for Standardization (ISO) was optimized and validated for quantitative determination of piperine in black pepper. The method was successfully validated for linearity, range, accuracy, precision, limit of detection, limit of quantitation, and measurement uncertainty. The validated method was used for the analysis of nine black pepper samples collected from the local supermarket of Kathmandu. The piperine content of the samples collected from various areas of Kathmandu, Nepal were found in the range of 2.33 % to 3.34 % with an average of 2.75 % and a standard deviation of 0.31%. This simple, precise, and accurate method can be used for routine analysis of piperine content in black pepper for quality control purposes.